Handbook of Research on the Global View of Open Access and Scholarly Communications. - Alemneh, Daniel Gelaw. (IGI Global, 2022)
In an information and knowledge society, access to information and knowledge is a basic human right, making equitable and fair access to information and knowledge paramount. Open Access (OA) plays a huge role in addressing inequities as well as broad-based and inclusive scientific progress. On the surface, the number of publications discussing OA issues from various angles are on the rise. However, what is missing is a comprehensive assessment of the extent of OA implementation and a discussion of how to proceed in integrating OA issues from various perspectives. The Handbook of Research on the Global View of Open Access and Scholarly Communications articulates OA concepts and issues while demystifying the state-of-the-art knowledge domain in the areas of OA and scholarly communications from diverse perspectives as well as implications for the information and knowledge society. Covering topics such as ethics, copyright challenges, and open access initiatives, this book is a dynamic resource for publishers, librarians, higher education administrators, policymakers, students and educators of higher education, researchers, and academicians.